Treatment strategies and survival of older breast cancer patients - an international comparison between the Netherlands and Ireland. - Mandy Kiderlen; Paul M Walsh; Esther Bastiaannet; Maria B Kelly; Riccardo A Audisio; Petra G Boelens; Chris Brown; Olaf M Dekkers; Anton J M de Craen; Cornelis J H van de Velde; Gerrit-Jan Liefers (PLoS ONE, 2015)
Objectives Forty percent of breast cancers occur among older patients. Unfortunately, there is a lack of evidence for treatment guidelines for older breast cancer patients. The aim of this study is to compare treatment strategy and relative survival for operable breast cancer in the elderly between The Netherlands and Ireland. Material and methods From the Dutch and Irish national cancer registries, women aged ≥65 years with non-metastatic breast cancer were included (2001-2009). Proportions of patients receiving guideline-adherent locoregional treatment, endocrine therapy, and chemotherapy were calculated and compared between the countries by stage. Secondly, 5-year relative survival was calculated by stage and compared between countries. Results Overall, 41,055 patients from The Netherlands and 5,826 patients from Ireland were included. Overall, more patients received guideline-adherent locoregional treatment in The Netherlands, overall (80% vs. 68%, adjusted p<0.001), stage I (83% vs. 65%, p<0.001), stage II (80% vs. 74%, p<0.001) and stage III (74% vs. 57%, P<0.001) disease. On the other hand, more systemic treatment was provided in Ireland, where endocrine therapy was prescribed to 92% of hormone receptor-positive patients, compared to 59% in The Netherlands. In The Netherlands, only 6% received chemotherapy, as compared 24% in Ireland. But relative survival was poorer in Ireland (5 years relative survival 89% vs. 83%), especially in stage II (87% vs. 85%) and stage III (61% vs. 58%) patients. Conclusion Treatment for older breast cancer patients differed significantly on all treatment modalities between The Netherlands and Ireland. More locoregional treatment was provided in The Netherlands, and more systemic therapy was provided in Ireland. Relative survival for Irish patients was worse than for their Dutch counterparts. This finding should be a strong recommendation to study breast cancer treatment and survival internationally, with the ultimate goal to equalize the survival rates for breast cancer patients across Europe.